A Produtividade na Bovinocultura de Corte e o Efeito Poupa-terra no período 1950-2017 - Nascimento, Cyro Guimarães Ribeiro do (2021)
Brazil is able to produce and meet its beef needs and global demands, for this purpose, the understanding of the benefits of using technologies and knowledge is necessary and strategic. Sustainability is a key factor for the entire chain and the national beef cattle farming has the technological conditions to preserve biodiversity, the environment, sustain its economic growth, increase its production, and thus directly impact the entire society in a positive way and demystify the erroneous thinking that beef cattle raising is a low-productive activity and costly to the environment. When beef cattle farming is used in an intensive form, it provides a reduction in area and gains in productivity. This turns the activity more efficient, sustainable, leaving behind a past where new areas added to the production process were essential to increase productivity. The land-saving effect has been discussed since then, thanks to increased productivity with a reduction in pasture areas. In order to analyze the land-saving effect, it is necessary to understand the beef cattle farming retrospective, looking in the literature for the evolution of production systems, the implementation of technology in the field, animal nutrition, genetics, and animal welfare. This work aims to analyze the productivity and the land-saving effect generated in the period between 1950-2017 using as a strategy the development of a database with the variables that make up a historical series on beef cattle, to identify the behaviors that impact productivity and thus to verify if there was a land-saving effect and what is its dimension. Data for discussion were obtained from the IBGE Census. For data analysis, models of linear equations and distributive functions were used. The results indicate a total of 603 million hectares saved over the years, showing that there was an evolution in the production process. They also demonstrate that with the implementation of public policies that encourage the intensification of production systems, it is possible to generate growth in the land-saving effect, increasing productivity in each region. It is necessary to expand the discussion on land use in beef cattle farming, as its heterogeneous production involves small producers with rudimentary methods and intensive beef cattle farming.